Oxidized LDL lipids as a risk factor for atherosclerosis - Linna, Meri (Annales Universitatis Turkuensis D 1150, 2014)
University of Turku, Faculty of Medicine, Department of Clinical Medicine, Department of Physical Activity and Health, Paavo Nurmi Centre, Doctoral Programme of Clinical Investigation, University of Turku, Turku, Finland. Annales Universitatis Turkuensis. Medica – Odontologica, Turku, Finland, 2014. Background: Atherosclerosis progression spans an entire lifetime and has a wide pool of risk factors. Oxidized LDL (oxLDL) is a crucial element in the progression of atherosclerosis. As a rather new member in the atherosclerosis risk factor family, its interaction with the traditional pro-atherogenic contributors that occur at different ages is poorly known. Aims: The aim of this study was to investigate oxLDL and its relation to major contributing risk factors in estimating atherosclerosis risk in data consisting mostly of adult men. The study subjects of this study consisted of four different sets of data, one of which contained also women. The age range of participants was 18-100 years and totaled 2337 participants (of whom 69% were men). Data on anthropometric and hormonal parameters, laboratory measures and medical records were assessed during 1998-2009. Results: Obesity was paralleled with high concentrations of oxLDL, which consequentially was reduced by weight reduction. Importantly, successful weight maintenance preserveed this benefit. A shift from insulin sensitivity to insulin resistance increased oxLDL. Smokers had more oxLDL than non-smokers. A combination of obesity and smoking, or smoking and low serum total testosterone,resulted in even higher levels of oxLDL than any of the three conditions alone. Proportioning oxLDL to HDL-c or apoA1 stood out as a risk factor of all-cause mortality in the elderly. Conclusions: OxLDL was associated with aging, androgens, smoking, obesity, insulin metabolism, weight balance and other circulating lipid classes. Through this variety of metabolic environments containing both constant conditions (aging and gender) as well as lifestyle issues, these findings supported an essential and multidimensional role that oxLDL plays in atherosclerosis pathogenesis.

Paavo Nurmi -keskus ja Terveysliikunnan oppiaine, Turun yliopisto, Turku. Annales Universitatis Turkuensis. Medica – Odontologica, Turku, 2014. Tausta: Valtimoiden kovettuminen on tapahtuma, joka kehittyy tunnetusti koko eliniän ajan. Valtimokovettumataudille on tyypillistä myös se, että sillä on runsaasti riskitekijöitä. Hapettunut LDL on yksi keskeinen elementti valtimoiden kovettumisessa. Verraten uutena riskitekijänä sen rooli muiden valtimonkovettumatautia edistävien riskitekijöiden joukossa on merkittävältä osin vielä epäselvää. Tavoitteet: Väitöskirjatyön tavoitteena on ollut tutkia hapettuneen LDL:n yhteyttä muihin merkittäviin valtimonkovettumatautia kuvaaviin riskitekijöihin aikuisiällä. Tutkimuksen koehenkilöt muodostuivat neljän eri aineiston pohjalta, joista yhdessä mukana on myös naisia. Yhteensä 2337 koehenkilön (joista 69% miehiä) ikähaitari oli 18-100 vuotta. Kehon koostumukseen, elintapoihin, verestä mitattaviin laboratoriomittauksiin sekä sairauskertomustietoihin liittyvät tarvittavat muuttujat kerättiin vuosina 1998-2009. Tulokset: Liikapainoon liittyy suurentunut oxLDL –pitoisuus. Laihduttaminen pienentää oxLDL –pitoisuuksia merkittävästi, ja onnistunut painonhallinta myös ylläpitää tämän alentuneen tason. Insuliiniresistenssi on yhteydessä oxLDL – pitoisuuksien kohoamiseen. Tupakoivien oxLDL –pitoisuudet ovat korkeammat kuin tupakoimattomien. Liikapainon ja tupakoinnin tai tupakoinnin ja matalan seerumin kokonaistestosteronipitoisuuden yhdistelmä johtaa korkeampiin oxLDL –pitoisuuksiin kuin mikään näistä kolmesta tekijästä yksinään. Mitä suurempi vyötärön ympärysmitta, sitä korkeammat pitoisuudet oxLDL:ää. OxLDL:n ja HDL –kolesterolin välinensuhdelukuennustaaosaltaanmerkittävästi kokonaiskuolleisuutta iäkkäillä. Johtopäätökset: Ikääntyminen, androgeenistatus, tupakointi, liikapaino, insuliiniaineenvaihdunta, painon hallinta ja seerumin muut lipidit näyttävät vuorovaikuttavan LDL-partikkelin sisältämien lipidien hapettumisen kanssa. Näiden useiden eri aineenvaihduntareittien sisältäessä sekä vakiona pysyviä tekijöitä (ikääntyminen, sukupuoli) että muuttuvia (elintavat), tässä väitöskirjassa esitetyt tulokset tukevat oxLDL:n moniulotteista ja keskeistä roolia valtimoiden kovettumisessa.